Are they All in the Same Boat? : The 2000-2001 Growth Slowdown and the G-7 Business Cycle Linkages - Helbling, Thomas (IMF Working Papers; Working Paper ;, 2003)
This paper reviews the international business cycle among Group of Seven (G-7) countries since 1973 from two angles. An examination of business cycle synchronization among these countries using simple descriptive statistics shows that synchronized slowdowns have been the norm rather than the exception and that the slowdown in 2000-2001 largely followed patterns seen in the past. The paper also identifies the international business cycle with an asymptotic dynamic factor model. Two global factors explain roughly 80 percent of the variance in G-7 output gaps at business cycle frequencies. The factor model decomposes the "common part" of national output fluctuations into two factors, one capturing the average G-7 cycle and one that corrects for phase and amplitude differences. We also found some evidence supporting the hypothesis that global shocks were the main force behind the slowdown in 2000-2001.